Study on the Influence of Different Peri-Implant Mucosa Cleaning Protocols on Microbial Biofilm Formation - Mukesh Soni; Shivani Mishra; Madhu S. Ratre; Sadaf Kazmi; Shivani Aditi; Suruchi Singh (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: The accumulation of microbial biofilm around dental implants remains a significant concern in maintaining peri-implant health. Ineffective cleaning of the peri-implant mucosa can result in peri-implantitis, jeopardizing implant longevity. This study evaluates the influence of different peri-implant mucosa cleaning protocols on microbial biofilm formation. Materials and Methods: A total of 60 patients with dental implants were included in this randomized controlled trial. Participants were divided into three groups (n = 20 per group) based on the cleaning protocol: Group 1 (manual brushing with soft bristles), Group 2 (ultrasonic cleaning), and Group 3 (air polishing). Biofilm accumulation was assessed at baseline, 1 month, and 3 months using the Plaque Index (PI) and microbial colony-forming units (CFU). Statistical analysis was performed using one-way ANOVA to determine significant differences between groups. Results: At the end of the study, Group 3 (air polishing) demonstrated the least biofilm accumulation, with a mean PI score reduction of 70% compared to baseline. Group 2 (ultrasonic cleaning) showed a 50% reduction, whereas Group 1 (manual brushing) exhibited a 30% reduction. Microbial analysis revealed the lowest CFU counts in Group 3 (1500 ± 200 CFU), followed by Group 2 (3200 ± 300 CFU) and Group 1 (5000 ± 400 CFU). Statistically significant differences (P < 0.05) were observed between the groups at 1 and 3 months. Conclusion: Air polishing proved to be the most effective peri-implant mucosa cleaning protocol for reducing microbial biofilm formation, followed by ultrasonic cleaning. Manual brushing alone showed limited efficacy in controlling biofilm. Implementing efficient cleaning protocols is crucial for preventing peri-implant diseases and enhancing implant success.